Cross-Validation of Paranoid and Depressive Scales: Results From Functional MRI Group Independent Component Analysis - Drozdstoy Stoyanov; Rossitsa Paunova; Diyana Najar; Gabriela Zlateva; Sevdalina Kandilarova; Vladimir Khorev; Semen A. Kurkin (Mental Illness)
Conclusion: Our results demonstrate differences in brain circuits processing preferentially diagnostic stimuli across the three groups. Those circuits involve mainly networks of cognitive and affective functioning, which provides insights in their role for pathophysiology of SCZ and DEP. This evidence fosters the theory of transdisciplinary validation, where neurobiological measure such as functional MRI is determined as external validity operation for the diagnostic assessment scales. This can facilitate the use of clinical evaluation methods as proxy measures of brain functions.